PENGARUH KUALITAS PRODUK DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN RUMAH MAKAN SUP TUNJANG DWI SIDOMULYO KECAMTAN LIRIK - Alvionita Rina Mei; Nursanti Aida; Promalessy Rika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to find empirical evidence related to the influence ofproduct quality, location on purchasing decisions and consumer satisfaction atthe Sup Tunjang Dwi Sidomulyo restaurant,Lyrics sub-district. The population ofthis study were all customers or consumers who had bought at the Tunjang DwiSidomulyo Soup Restaurant,Lyrics sub-district. The sample of this study wasselected using the sampling technique used, namely Probability Sampling usingthe Slovin formula of 10%. that is as many as 102 samples. Hypothesis testing wascarried out with the help of the SPSS 25 statistical test tool, while the data usedwas a questionnaire that had been filled out by each consuming Sup Tunjang DwiSidomulyo restaurant,Lyrics district. The results of this study indicate that 1)product quality affects purchasing decisions, 2) location affects purchasingdecisions, 3) product quality affects consumer satisfaction through purchasingdecisions, 4) location affects consumer satisfaction through purchasing decisions,5) decisions affect consumer satisfaction through purchasing decisions. consumersatisfaction. Keywords: product quality, location, purchasing decisions, consumer satisfaction.